MiR-139-5p inhibits migration and invasion of colorectal cancer by downregulating AMFR and NOTCH1. Issue 11 (23rd August 2014) - Song, Mingxu; Yin, Yuan; Zhang, Jiwei; Zhang, Binbin; Bian, Zehua; Quan, Chao; Zhou, Leyuan; Hu, Yaling; Wang, Qifeng; Ni, Shujuan; Fei, Bojian; Wang, Weili; et al.
Abstract: MicroRNAs (miRNAs) that exert function by posttranscriptional suppression have recently brought insight in our understanding of the role of non-protein-coding RNAs in carcinogenesis and metastasis. In this study, we described the function and molecular mechanism of miR-139-5p in colorectal cancer (CRC) and its potential clinical application in CRC. We found that miR-139-5p was significantly downregulated in 73.8% CRC samples compared with adjacent noncancerous tissues (NCTs), and decreased miR-139-5p was associated with poor prognosis. Functional analyses demonstrated that ectopic expression of miR-139-5p suppressed CRC cell migration and invasion in vitro and metastasis in vivo. Mechanistic investigations revealed that miR-139-5p suppress CRC cell invasion and metastasis by targeting AMFR and NOTCH1. Knockdown of the two genes phenocopied the inhibitory effect of miR-139-5p on CRC metastasis. Furthermore, the protein levels of the two genes were upregulated in CRC samples compared with NCTs, and inversely correlated with the miR-139-5p expression. Increased NOTCH1 protein expression was correlated with poor prognosis of CRC patients. Together, our data indicate that miR-139-5p is a potential tumor suppressor and prognostic factor for CRC, and targeting miR-139-5p may repress the metastasis of CRC and improve survival.